2022
DOI: 10.31157/an.v27i2.331
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of dehydroepiandrosterone for Parkinson's disease: scoping review protocol

Abstract: Background: Parkinson's disease (PD) is a neurodegenerative disorder characterized by a progressive loss of nigrostriatal dopaminergic neurons. Its treatment is symptomatic and shows limited efficacy. Dehydroepiandrosterone (DHEA) is a hormone produced in the brain. Several studies have reported beneficial effects of the steroid in experimental models of PD and various human diseases, but its potential for PD is inconclusive. Therefore, it is necessary to evaluate current evidence to determine the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This methodology is based on a preceding protocol, 22 but it is not an update of any previous review. After elaborating on the research question, we used an online tool to define the most appropriate type of review, as previously reported, 23 which was scoping review (https:// whatreviewisrightforyou.knowledgetranslation.net/map/ results?id=5413&code=GAkWQRoevx).…”
Section: Protocol Developmentmentioning
confidence: 99%
“…This methodology is based on a preceding protocol, 22 but it is not an update of any previous review. After elaborating on the research question, we used an online tool to define the most appropriate type of review, as previously reported, 23 which was scoping review (https:// whatreviewisrightforyou.knowledgetranslation.net/map/ results?id=5413&code=GAkWQRoevx).…”
Section: Protocol Developmentmentioning
confidence: 99%